Probabilistic Unit Commitment with Wind Farms Considerations - Hosseini, S.H.; Abbasi, E. (2007 Large Engineering Systems Conference on Electric Power Engineering, 2007)
This paper proposes a method for unit commitment in restructured power systems with high penetration of wind farms. As wind is an intermittent source of energy and can not be predicted with high accuracy, reliability of wind farms compare to conventional power plants is lower. By increasing penetration of wind farms in generation system, reliability of power system will decrease. Therefore, reliability constraint should be added to unit commitment (UC) formulation. On the other hand, wind is a green source of energy; additionally environmental crisis is very important issue in the 21 st century. By adding emission constraint to UC, wind energy will be valued. Both reliability and emission constraints are acing as fuzzy constraints. It means that if the UC solution exceeds these constraints limits, that configuration of UC will be penalized by adding augmented cost to total UC cost. To implement these constraints to UC, simulated annealing (SA) has been used because it converges very well under complex and nonlinear constraints. At the end, if any wind farm considered to be off in UC, a must run constraint will make them on and calculate reliability effect of the recommitted wind farm on generation system and decrease from the capacity of the most expensive thermal units equal to the calculated effect of newly committed wind farm on system reliability. Then wind farms that recommitted will be paid 80 percent of the cheapest committed unit in that period. In this way, wind farms will be supported wisely and free power market conditions will be remain unchanged.